IJTIHAD DALAM PERSPEKTIF ULAMA’ SYI’AH ISNA ‘ASYARIYAH - Baharun, Mohammad (ULUL ALBAB Jurnal Studi Islam, 2007)
Basically, the perspective of Ulamaâ€™ Syiah Isna â€˜asyariyah about jihad is not different from Sunniâ€™s perspective. Other side, still there different between them and this become something that â€œmust beâ€ there for them.Ulamaâ€™ Syiâ€™ah Isna â€˜Asyariyah said taht the main of jihad are Imamah and all of this its implications, which are placed in the central position os Syiâ€™ahâ€™s thought. However, that thought differentiates Syiâ€™ah and Ahl Sunnah wa al-Jamaâ€™ah themselves.Imamah is a concept of leadership after the death of Muhammad SAW, it convinced as the certainly of religion. Imamah is supported by Ijtihad of Ulamaâ€™ Syiâ€™ah Isna â€˜asyariyah intensively to strength the argumentation of Imamah certainly. The Ijtihad elaboration about imamah becomes a concept of Marjaâ€™iyat-i-Taqlid and Wilayat-i-Faqih. It is very important to Syiâ€™ah, because the highest Mujtahid/Marjaâ€™ is as the changer of Imam Mahdi. Ijtihad Imamah related to the perspective of Ulamaâ€™ Syiâ€™ah Isna â€˜Asyariyah ulama is something certainly. The implication of imamah is the birth of theories, such as, â€˜ismah, taqiyah, Marjaâ€™iyat-i-taqlid and Wilayat-i-Faqih. And all of these are the consequence of Ghaibat al-Imam (themystery of Imam Mahdi).